NILAI SOSIAL PADA NOVEL “SUNSET BERSAMA ROSIE” KARYA TERE LIYE - Sofyan Arif Miftahuddin Sofyan (Bahtera: Jurnal Pendidikan Bahasa dan Sastra, 2021)
ABSTRACT The purpose of this research is to describe the social values ​​contained in Novel Sunset with Tere Liye's Rosie. This research is a qualitative research. The steps carried out in this study are to describe the data objectively according to the data that has been found. This research has resulted in findings in the form of social values ​​(1) affection (Love) which include devotion, helping, kinship, loyalty, concern then (2) the value of responsibility (Responsibility) which includes responsibility to family, responsibility to society, and responsibility to God, it can be concluded that the novel Sunset Bersama Rosie by Tere Liye has life values ​​that can be applied in social life. Keywords: Value, Social, Novel